Pengaruh Pijat Efflurage Terhadap Tingkat Kecemasan Pada Ibu Post Partum - Luh Komang Suwarmasanti; Putu Ayu Ratna Darmayanti; Ni Komang Sri ariani; I Dewa Ayu Agra Darmawati (Journal of Innovative and Creativity, 2026)
The postpartum period is a transitional phase characterized by physiological recovery and psychological adaptation, which may increase vulnerability to anxiety. Postpartum anxiety can interfere with maternal emotional stability and caregiving ability if not properly managed. Complementary therapies, such as effleurage massage, are considered safe non-pharmacological interventions that may promote relaxation and reduce anxiety levels. This study aimed to examine the effect of effleurage massage on anxiety levels among postpartum mothers. This study employed a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of postpartum mothers selected using a total sampling technique. Anxiety levels were measured using a structured questionnaire, and data were analyzed using the Wilcoxon test. Statistical analysis showed a significant decrease in anxiety levels following the administration of effleurage massage, with an Asymp. Sig. (2- tailed) value of 0.000 (p < 0.05). Effleurage massage significantly reduced anxiety levels among postpartum mothers. Future studies are recommended to explore psychological adaptation mechanisms in postpartum women related to anxiety reduction.